Biomass ash stabilized MgO adsorbents for CO2 capture application. (1st January 2020) - Guo, Yafei; Tan, Chang; Sun, Jian; Li, Weiling; Zhang, Jubing; Zhao, Chuanwen
Graphical abstract: Highlights: Biomass ash stabilized MgO adsorbents are prepared for CO2 capture. Effects of support and MgO loading on CO2 adsorption performance are discussed. MgO-RHA-20 exhibits excellent CO2 adsorption capacity of 4.56 mmol CO2 /g. The desired adsorbent shows favorable working stability in 10 repeated cycles. The scheme provides remarkable economic and environmental implications. Abstract: Supported MgO adsorbents were prepared from the calcination of MgCl2 ·6H2 O preloaded on several biomass wastes including sugarcane bagasse, coffee grounds, rice husk, and saw dust. CO2 adsorption behaviors of the adsorbents with different supports and MgO loadings were investigated using a fixed-bed reactor. The modified Avrami fractional kinetic model was adopted to correlate their CO2 uptakes to evaluate the CO2 adsorption kinetic performance. Amongst the prepared MgO adsorbents, the rice husk ash supported sample (MgO-RHA) featured high CO2 adsorption capacity, due to the good textural properties, nano-crystallization of MgO particles, the uniform dispersion of active components and the enriched surface basicity. CO2 uptakes of MgO-RHA increased first and then decreased with the increasing MgO loading. CO2 adsorption kinetic would be hampered by higher MgO contents because of the increased diffusion resistance and decreased MgO utilization. The adsorbent with 20 wt% MgO loading exhibited the highest CO2 uptake of 4.56 mmol CO2 /g. Besides, the desired adsorbent presented good working stability with 7.68% loss-in-capacity in 10 repeated cycles. Recycling waste MgCl2 ·6H2 O and biomass residues to synthesize CO2 adsorbents provides remarkable economic and environmental implications, from the prospective of CO2 emission mitigation and waste management.